Synthesis and Crystal Structure of Nickel(II) Complex: [Ni(phen)2(N3)2] - Bi, Wen-Jie; Dong, Hua-Ze (Asian Journal of Chemistry, 2014)
A novel nickel(II) complex [Ni(phen)2(N3)2] has been synthesized, with the 1,10-phenanthroline (phen) and the nitrine (N3-) as ligands and characterized by IR spectra and single-crystal X-ray diffraction measurements. The crystal is triclinic, space group P-1 with cell dimensions of a = 8.2079(7) Å, b = 11.0042(10) Å, c = 12.4317(11) Å, a = 82.259(2)º, b = 82.240(2)º, g = 72.5150(10)º, V = 1055.88(16) Å3, Z = 2, Mr = 503.18, Dc = 1.583 mg/cm3, μ = 0.957 mm-1, F(000) = 516, T = 298(2) K, R = 0.0372, wR = 0.0948 for 5278 reflections with I > 2(I). In the molecular structure unit, nickel(II) cation is coordinated by six donor atoms and has a slightly distorted octahedron configuration.